2020
DOI: 10.1111/ijlh.13150
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of reference intervals for pediatric complete capillary blood counts: A multicenter study in Beijing

Abstract: Introduction Clinical reference intervals represent the normal range of clinical parameters for distinguishing healthy and sick individuals, and they show some variation among different populations. Many reference intervals are still lacking for the pediatric population in China. Thus, the aim of this study was to establish and validate pediatric reference intervals for capillary blood cell counts. Methods A total of 9942 children were enrolled from 10 medical institutions in Beijing, China, for capillary comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Other white blood cell‐related parameters, such as MONO# and MONO, were also relatively stable from 3 months to 18 years. LYM#, LYM, EO#, and EO gradually declined with age, and NEUT# and NEUT gradually increased with age; these trends were consistent with previous reports 6,17,18 . Gender differences were also observed in white blood cell‐related parameters.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Other white blood cell‐related parameters, such as MONO# and MONO, were also relatively stable from 3 months to 18 years. LYM#, LYM, EO#, and EO gradually declined with age, and NEUT# and NEUT gradually increased with age; these trends were consistent with previous reports 6,17,18 . Gender differences were also observed in white blood cell‐related parameters.…”
Section: Discussionsupporting
confidence: 91%
“…this trend was consistent with the study of Wang et al 7 Unlike most red blood cell-related parameters, MCV and MCH were higher in females than in males; a similar observation was also reported by with age; these trends were consistent with previous reports. 6,17,18 Gender differences were also observed in white blood cell-related parameters. The levels of WBC, MONO#, MONO, EO#, and EO before 10 years of age were higher in males than in females, and the differences in MONO#, MONO, EO#, and EO continued after 10 years.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…El‐Hazmi et al reported the difference of the RBC count, including RBC, Hb, MCV and MCH, between girls and boys did not show a significant change in the 1 to 13‐year‐olds 26 . Even though Sun et al and Wang et al reported the significantly difference of RBC, MCV and MCV between sex, except for Hb 11,12 . Obviously, the gender effect on the concentration of erythrocyte parameters should be explored on a larger sample size.…”
Section: Discussionmentioning
confidence: 97%
“…7,10 Laboratory results derived directly from reference intervals of adult can mislead clinical diagnosis and treatment, resulting in serious consequences. Although there have been preliminary studies on erythrocyte parameters for children in north China, 11,12 there is less information on erythrocyte and hemoglobin electrophoresis parameters for preschool children in Guangxi region of China. Therefore, establishing appropriate and accurate reference intervals of erythrocyte parameters and hemoglobin electrophoresis parameters, is of great significance for the prevention and treatment of hematological diseases and the accumulation of valuable genetic resources, and is also conducive to the screening of thalassemia in Guangxi.…”
Section: Introductionmentioning
confidence: 99%